The role of chloroquine phosphate on tumor necrosis factor - alpha and interleukin-one in knee osteoarthritic patients - Eman S. S.; Kismet M. T.; Mohammed H. M. (College of Pharmacy / Mustansiriyah University, 2010)
Osteoarthritis (OA) is a condition characterized by a series of inflammatory processes. Various pro inflammatory cytokines like interleukin- one (IL-1) and tumor necrosis factor-alpha (TNF-α) are present in synovium and tissue of rheumatic patients, so these agents play an essential role in pathogenesis of joint diseases. Chloroquine phosphate (CQP) interferes the cellular function of acid microenvironments such as lysosome, endosome and Golgi's complex, as well as affects pathways of inflammation, immune cascade and enzyme activity which ultimately resulted in cartilage destruction in knee joint with OA.